Cerebrospinal fluid HIV-1 escape according to different thresholds and underlying comorbidities: is it time to assess the definitions?. (15th March 2019) - Trunfio, Mattia; Pinnetti, Carmela; Focà, Emanuele; Bai, Francesca; Maffongelli, Gaetano; Celani, Luigi; Cinque, Paola; Celotti, Anna; Andreoni, Massimo; D'Arminio Monforte, Antonella; D'Ettorre, Gabriella; Antinori, Andrea; et al.
Abstract : N/A: No consensus has been reached on how to define cerebrospinal fluid HIV-1 escape (CSF-E). We describe its prevalence in 1095 paired CSF-plasma HIV-RNA measurements from antiretroviral-treated patients according to several definitions and neurological affections. CSF-E prevalence varied substantially (9.0–38.9%) and was higher in patients with cerebrovascular disorders, HIV-associated dementia and white matter abnormalities. Considering the variability in HIV-RNA quantification assays, the biological relevance of viral escape at different thresholds needs to be accurately assessed. Abstract : Supplemental Digital Content is available in the text